Looking Back, Looking Forward: A Retrospective Analysis of a Pre-service Teacher Preparation Course - Nancy Caukin; Heather Dillard; Terry Goodin; Ashlee Hover; John Carter (International Journal for the Scholarship of Teaching and Learning, 2022)
This SoTL study aimed to determine thirty-eight teacher candidates’ self-efficacy after experiencing semester one of a yearlong residency. Researchers used a pre/post survey, the Teachers’ Sense of Efficacy Scale (TSES), and a retrospective pre TSES to determine perceived levels of self-efficacy in three areas: classroom management, instructional strategies, and student engagement. Findings revealed that pre TSES (candidates scored themselves at the beginning of the semester) and retrospective pre TSES scores (candidates scored themselves at the end of the semester reflecting on where they were at the beginning of the semester) were significantly different, with the retrospective pre TSES showing lower self-efficacy than the pre TSES. Post TSES comparisons to the retro-spective pre TSES showed a significant increase, whereas, the comparison of the traditional pre/post TSES showed no significant changes. This suggests teacher candidates had an overinflated sense of self-efficacy and that teacher educators should look beyond the pre TSES to provide transformational experiences for teacher candidates. The retro-pre TSES helps teacher educators monitor teacher candidates’ change in self-efficacy and gauge program impact.